Influence of ion implantation and annealing on composition and structure of GaAs surface - Normuradov, M.T.; Umirzakov, B.E.; Tashmukhamedova, D.A.; Tashatov, A.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
In this work investigated is the influence of barium ion implantation and subsequent annealing on composition, electronic and crystalline structure of GaAs surface. For the first time, the influence of low energy Ba⁺ ions implantation on the structure of GaAs surface was investigated using photoelectron spectroscopy. Determined are parameters of energy bands and the crystalline lattice of the three-component system Ga₀.₆Ba₀.₄As. The width of the forbidden gap is Eg = 1 eV, the lattice constant is a = 5.73 Å.